How to solve -5x+2y =13 and 5x+y=-1 by elimination

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5



Oct 20th, 2017

To solve by elimination, you add or subtract the 2 equations to get rid of one of the variables.  Since one equation has a 5x term and the other has a -5x term, if we add the two questions together, we can eliminate x.

  -5x + 2y = 13

+ 5x  + y = -1

The x terms drop out and you're left with:

2y + y = 13 + -1

3y = 12

y = 4

Now, you substitute y into either one of the original equations to get x.

5x + y = -1

5x + 4 = -1

5x = -5

x = 1

Nov 13th, 2014

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
Oct 20th, 2017
Oct 20th, 2017
Oct 21st, 2017
Mark as Final Answer
Unmark as Final Answer
Final Answer

Secure Information

Content will be erased after question is completed.

Final Answer